The landscape of exosomal non-coding RNAs in breast cancer drug resistance, focusing on underlying molecular mechanisms - Rezaee, Malihe; Mohammadi, Fatemeh; Keshavarzmotamed, Atoosa; Yahyazadeh, Sheida; Vakili, Omid; Milasi, Yaser Eshaghi; Veisi, Vida; Dehmordi, Rohollah Mousavi; Asadi, Sepideh; Ghorbanhosseini, Seyedeh Sara; Rostami, Mehdi; Alimohammadi, Mina; et al. (Frontiers in Pharmacology, 2023)
Breast cancer (BC) is the most common malignancy among the female population worldwide. Like many other cancers, BC therapy is challenging and sometimes frustrating. In spite of the various therapeutic modalities applied to cease the cancer, drug resistance, a.k.a. chemoresistance, is very common in almost all BCs. Undesirably, a breast tumor might be resistant to different curative approaches (e.g. chemo- and immunotherapy) at the same period of time. Exosomes, as double membrane-bound extracellular vesicles (1) that are secreted from different cell species, can considerably transfer cell products and components through the bloodstream. In this context, non-coding RNAs (ncRNAs), including miRNAs, long ncRNAs (lncRNAs), circular RNAs (circRNAs), etc., are a chief group of exosomal constituents with amazing abilities of regulating BC underlying pathogenic mechanisms, such as cell proliferation, angiogenesis, invasion, metastasis, migration, and particularly drug resistance. Thereby, exosomal ncRNAs can be considered potential mediators of the BC progression and drug resistance. Moreover, as the corresponding exosomal ncRNAs are circulating in bloodstream and found in different body fluids, they can serve as foremost prognostic/diagnostic biomarkers. The current study aims to comprehensively review the most recent findings on the BC-related molecular mechanisms and signaling pathways affected by exosomal miRNAs, lncRNAs, and circRNAs, with a focus on drug resistance. Also, the potential of the same exosomal ncRNAs in diagnosis and prognosis of BC will be discussed in detail.